KETERKAITAN STANDAR PELAYANAN MINIMAL (SPM) DENGAN STANDAR NASIONAL PENDIDIKAN (SNP) - Jafriansen Damanik (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2017)
ABSTRACT Many sides quest on the needs of two standards in implementing education in Indonesia, they are Minimum Service Standards (MSS) and National Education Standards (NES). This article is aimed at discussing the relation between MSS and NES through goverment regulation and related program. In the goverment regulation itself, it is told that the fulfilment of MSS is the initial requirement of the fulfilment of NES. In relation with accreditation instruments as a measurement or assestment tool on the fulfilment of NES, it is proved that all indicators of MSS of primary education by educational unit are also found in accreditation instrument. Some indicators of MSS issued by district goverment are also relevant with accreditation instrument. The difference just belongs to the way to assest and measure the fulfilment standard. The instrument of MSS uses an absolute assestment, in the mean time accreditation instrument uses an interval scale. This action creates the existence of an accredited school but it does not fulfil the MSS yet. Basically, MSS and NES are closely related since both of them are quality assurance of public school or school madrasahs. The MSS are required to meet especially by the goverment of district city by means to be improved in order to fulfil even to exceed the NES. The fulfilment of MSS and NES must be implemented periodically as a mutual responsiblity of educational unit, goverment and private educational institutions, the district and central goverment. Keywords: minimum service standards, national education standards, the connection. ABSTRAK Banyak pihak yang mempertanyakan perlunya dua standar dalam bidang pendidikan di Indonesia, yakni Standar Pelayanan Minimal (SPM) dan Standar Nasional Pendidikan (SNP). Tulisan ini dimaksudkan untuk membahas keterkaitan antara SPM dengan SNP, melalui peraturan dan program yang terkait. Dalam peraturan disebutkan bahwa pemenuhan SPM merupakan syarat awal pemenuhan SNP. Terkait dengan instrumen akreditasi sebagai alat ukur pemenuhan SNP, ternyata seluruh indikator SPM Dikdas oleh satuan pendidikan terdapat juga dalam instrumen akreditasi. Beberapa indikator SPM oleh pemerintah kab./kota juga relevan dengan instrumen akreditasi. Perbedaannya terletak cara penilaian atau pengukuran pemenuhan standar. Instrumen SPM menggunakan penilaian absolut atau mutlak, sementara instrumen akreditasi menggunakan skala interval. Hal ini menyebabkan adanya sekolah yang terakreditasi tetapi belum memenuhi SPM. Pada dasarnya SPM dan SNP sangat terkait, karena keduanya merupakan ukuran mutu sekolah/madrasah. SPM diupayakan pemenuhannya terutama oleh pemerintah daerah, untuk selanjutnya ditingkatkan hingga memenuhi bahkan melampaui SNP. SPM maupun SNP harus diupayakan pemenuhannya secara bertahap, sebagai tanggungjawab bersama satuan pendidikan, lembaga penyelenggara pendidikan swasta, pemerintah daerah dan pemerintah pusat. Kata kunci: standar pelayanan minimal, standar nasional pendidikan, keterkaitan.